2007
DOI: 10.1016/j.heares.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Excitatory, inhibitory and facilitatory frequency response areas in the inferior colliculus of hearing impaired mice

Abstract: Individuals with age-related hearing loss often have difficulty understanding complex sounds such as basic speech. The C57BL/6 mouse suffers from progressive sensorineural hearing loss and thus is an effective tool for dissecting the neural mechanisms underlying changes in complex sound processing observed in humans. Neural mechanisms important for processing complex sounds include multiple tuning and combination sensitivity, and these responses are common in the inferior colliculus (IC) of normal hearing mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…A similar situation exists in another species, in mice: hearing function in the CBA/CaJ strain of mice deteriorates very slowly as in the Long-Evans strain of rats, whereas the C57BL/6J strain is known to undergo rapid deterioration with early deafness (Parham, 1997, Spongr et al, 1997. In spite of these differences in age-related defects of auditory function, which are mostly caused by pathologies in the inner ear, significant age-related alterations of the inhibitory function in the central auditory system were reported in both strains of mice (Walton et al, 1998(Walton et al, , 2002Felix and Portfors, 2007). Therefore, we may tentatively suggest that the age-related decline in GAD expression in the IC and AC demonstrated in our experiments does not depend primarily on peripheral deafferentation but is, at least partially, of central origin.…”
Section: Discussionmentioning
confidence: 99%
“…A similar situation exists in another species, in mice: hearing function in the CBA/CaJ strain of mice deteriorates very slowly as in the Long-Evans strain of rats, whereas the C57BL/6J strain is known to undergo rapid deterioration with early deafness (Parham, 1997, Spongr et al, 1997. In spite of these differences in age-related defects of auditory function, which are mostly caused by pathologies in the inner ear, significant age-related alterations of the inhibitory function in the central auditory system were reported in both strains of mice (Walton et al, 1998(Walton et al, , 2002Felix and Portfors, 2007). Therefore, we may tentatively suggest that the age-related decline in GAD expression in the IC and AC demonstrated in our experiments does not depend primarily on peripheral deafferentation but is, at least partially, of central origin.…”
Section: Discussionmentioning
confidence: 99%
“…3). This behavior could be produced by facilitatory mechanisms in the IC as they are reported for bats (e.g., Portfors and Wenstrup 2002) and rodents (Egorova et al 2001;Felix and Portfors 2007). In a study on mice, Portfors and Felix (2005) could demonstrate that 16% of the neurons had a response rate increase of Ն20% during presentation of an additional high-frequency tone.…”
Section: Inhibition and Facilitation Of The Neuronal Dp Responsementioning
confidence: 68%
“…Multiple tuned and combination-sensitive neurons are found in the IC of both mustached bats [26] and mice [27]. Felix and Portfors (2007) found that the majority of combination-sensitive and multiple tuned neurons are sensitive to high frequencies which led them to suggest that response properties of these types of neurons will be affected by age-related high frequency hearing loss. They further hypothesized that high frequency hearing loss reduces spectral integration properties in the IC.…”
Section: Discussionmentioning
confidence: 99%
“…Within the central auditory system the IC, the principal midbrain nucleus of the auditory pathway, has been described to undergo morphological and functional changes underlying age-related hearing loss [13,14]. To identify potential target genes for Tff3 in the IC we used a microarray-based screen.…”
Section: A Microarray-based Screen For Tff3-regulated Genes During Prmentioning
confidence: 99%
See 1 more Smart Citation